Reduced FGF9 leads to kidney injury through regulating renal tubular epithelial cell EMT in diabetes - Chen, Wen-qing; Sun, Chengyang; Zhang, Xiaotan; Ye, Xunjia; Liu, Yuzhen; Wang, Hui-di; Liu, Lichao; Li, Danrui; Wang, Jingyun; Shi, Meiting; Yang, Fang; Reichetzeder, Christoph; et al. (Journal of cellular and molecular medicine, 2025)
Diabetic nephropathy (DN) stands out as one of the most prevalent and severe chronic microvascular complications associated with diabetes, serving as the primary cause of end-stage renal disease (ESRD) in developed and developing countries. However, the precise pathogenesis remains incompletely elucidated. Our study suggests FGF9 as a key gene in DN using bioinformatics analysis. We found a negative correlation between FGF9 and serum creatinine and a positive one with glomerular filtration rate in DN patients. FGF9 expression was lower in DN patients' glomeruli and tubules. High FGFR expression in renal tubular cells, along with increased α-SMA and TGF-β1, indicates a role for the epithelial-to-mesenchymal transition (EMT) process in diabetes mellitus (DM) mouse renal tubular epithelial cells. Subsequently, we modulated FGF9 in HK2 cells under different glucose conditions. The genes regulated by FGF9 were identified (LOX, HIF1α, THBS1, TGFβ2 and ITGβ1) through RNA sequencing analysis. It was suggested that FGF9 promotes the development of renal EMT probably through regulating these genes. Overall, FGF9 could be a biomarker and therapeutic target for DN.